Performance of asphalt mixtures containing steel slag aggregate and synthetic fibers - Hezam Alnadish, Adham Mohammed (2019)
Utilization of waste materials in civil engineering applications has been documented as an effective method to preserve environment and natural resources. One of the well-known waste materials is steel slag aggregate, which is a byproduct of steel manufacturing. However, volume instability and high density are the main drawbacks of using steel slag aggregates. In this study, steel slag aggregates were immersed in water for six months to minimize the free lime and free magnesia content, which are mainly responsible for the volume instability. Furthermore, the granite aggregates were replaced by electric arc furnace (EAF) steel slag aggregate with different proportions to identify the suitable substitution in terms of superior performance. Subsequently, the asphalt mixtures incorporated the appropriate proportion of the steel slag aggregates were reinforced with polyvinyl alcohol (PVA), acrylic, and polyester fibers at different dosages of 0.05, 0.15, and 0.3% by weight of the aggregates, respectively. The conducted performance tests were resilient modulus, dynamic creep, rutting depth, moisture susceptibility, and cracking resistance. The findings of this study showed that the free lime and free magnesia content in the treated steel slag aggregate have significantly decreased. On the other hand, the asphalt mixtures incorporated coarse steel slag aggregate exhibited the best performance than the other substitutions. Furthermore, introducing synthetic fibers have dramatically enhanced the cracking resistance. The higher the fiber content, the higher the resistance to cracking. Additionally, the outputs of the permanent deformation tests showed that as the fibers dosages increase, the deformation increases due to the densification. Moreover, the asphalt mixtures performance incorporating 0.15% of synthetic fibers possesses the ability to decrease the thickness of the asphalt layer by about 10%. In conclusion, improving the performance of asphalt mixtures through utilization of steel slag aggregate and synthetic fibers is a successful approach in terms of extending the service life of asphalt layer.